The Effectiveness Of The Hypothetical Learning Model In Improving Students’ Abilities In Fiqh Subject At Ma Al-Ishlahiyah Binjai - Sintia Sintia; Satriyadi Satriyadi (The Islamic Education and Multiculturalism Foundation, 2026)
Abstrak Penelitian ini bertujuan untuk menguji efektivitas model Hypothetical Learning terhadap peningkatan kemampuan siswa pada mata pelajaran Fiqih di MA Al-Ishlahiyah Binjai, mengingat pembelajaran Fiqih masih cenderung menekankan hafalan dan kurang mengembangkan penalaran siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen yang melibatkan dua kelompok, yaitu kelas eksperimen dan kelas kontrol, masing-masing berjumlah 30 siswa. Kelas eksperimen menggunakan model Hypothetical Learning, sedangkan kelas kontrol menggunakan pembelajaran konvensional. Pengumpulan data dilakukan melalui tes hasil belajar dalam bentuk pretest dan posttest yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan statistik deskriptif dan inferensial, meliputi uji normalitas, homogenitas, dan uji t. Hasil penelitian menunjukkan bahwa nilai rata-rata posttest kelas eksperimen sebesar 81,25 lebih tinggi dibandingkan kelas kontrol sebesar 72,10, dengan nilai signifikansi 0,001 (<0,05). Temuan ini menunjukkan bahwa model Hypothetical Learning efektif meningkatkan kemampuan siswa. Novelty penelitian ini terletak pada penerapan model Hypothetical Learning dalam pembelajaran Fiqih yang menekankan penalaran hipotesis dan pemahaman konseptual siswa. Kata Kunci: Hypothetical Learning, Hasil Belajar, Pembelajaran Fiqih, Quasi Eksperimen Abstract This study aims to examine the effectiveness of the Hypothetical Learning model in improving students’ abilities in Fiqh subjects at MA Al-Ishlahiyah Binjai, considering that Fiqh learning still tends to emphasize memorization and provides limited opportunities for the development of students’ reasoning skills. This research employed a quantitative approach with a quasi-experimental design involving two groups, namely an experimental group and a control group, each consisting of 30 students. The experimental group was taught using the Hypothetical Learning model, while the control group received conventional instruction. Data were collected through achievement tests in the form of pretests and posttests that had been validated and tested for reliability. Data analysis was conducted using descriptive and inferential statistics, including normality and homogeneity tests, followed by hypothesis testing using an independent samples t-test. The results showed that the mean posttest score of the experimental group (81.25) was higher than that of the control group (72.10), with a significance value of 0.001 (p < 0.05). These findings indicate that the Hypothetical Learning model is effective in improving students’ abilities. The novelty of this study lies in the application of the Hypothetical Learning model in Fiqh instruction, emphasizing the development of hypothetical reasoning and students’ conceptual understanding. Keywords: Hypothetical Learning, learning outcomes, Fiqh learning, quasi-experimental design